7y-4x-5=0

Simple and best practice solution for 7y-4x-5=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7y-4x-5=0 equation:


Simplifying
7y + -4x + -5 = 0

Reorder the terms:
-5 + -4x + 7y = 0

Solving
-5 + -4x + 7y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + -4x + 5 + 7y = 0 + 5

Reorder the terms:
-5 + 5 + -4x + 7y = 0 + 5

Combine like terms: -5 + 5 = 0
0 + -4x + 7y = 0 + 5
-4x + 7y = 0 + 5

Combine like terms: 0 + 5 = 5
-4x + 7y = 5

Add '-7y' to each side of the equation.
-4x + 7y + -7y = 5 + -7y

Combine like terms: 7y + -7y = 0
-4x + 0 = 5 + -7y
-4x = 5 + -7y

Divide each side by '-4'.
x = -1.25 + 1.75y

Simplifying
x = -1.25 + 1.75y

See similar equations:

| -6=-10w+9 | | 2w+4=2+6 | | (X^2+x-6)/(3x+3)*(x+1)/(x^2+2x-3) | | 3(2x-3)+2x=15 | | 5u^2=7u+6 | | 3v^2-3=240 | | (5x^6)(8)= | | 8-1x=-5 | | (5x^6)*(8)= | | (3/5)x+4=(1/5)x+5 | | 10-0.6-3.1= | | (2a^3+a-4)-(3-4a^3-9a^2)= | | 9e^8x/5x+3 | | (3x+2)+(x+6)= | | -175+219= | | 2w^2-180w+2800=0 | | t^5*t^6= | | 5/6-5/9/4/5 | | 4x^2(x-5)= | | 5x^2-2x-6=-3x^2+2x | | ln=5(x+1) | | 1/3(2x-7)=3 | | 20=5.2x-08 | | w=5y+8 | | 20=5.2-0.8 | | 1/4(-4)=y | | 3(p+20)=81 | | 1/4(-8)=y | | 5d+4-(4d+2)= | | g(x)=-6x^2+5x+5 | | 3(2+s)=36 | | -8x-7x=-60 |

Equations solver categories